(untitled) (Sains Humanika, 2018)
Digital games are able to develop students’ skills that are accordance with 21st century skills. There are various types of digital games that can be used in today’s classroom. However, the challenge is how to choose a digital game that matches with the learning objectives and the desired curriculum. Therefore, this article will discuss how digital game selection can be made and what features should be taken into account when choosing digital games. The games used in this study is a logical game used as a medium to encourage students to think in developing their creativity when solving mathematics problem solving questions. This article also discusses about the selection of games that are made based on the features introduced in ’Magic Bullet’ which are the things that need to be learnt, and the things that can be learnt. The findings of the students’ feedback were also discussed in the study as it gives insights on the implementation of digital games in the classroom. In sum, the students stated that they can learn through the use of digital games and they realized that the problem-solving strategy could help them to solve problems they have faced and learning with peers also assist them to solve given problems. It is hoped that this article can provide guideline for researchers and teachers in selecting appropriate digital games that can be used in the classroom so that the objective of learning can be achieved.